Burgeoning Irrational Antibiotics use in Primary Health Care in Nepal - Shrestha, Shumneva; Yadav, Randhir Sagar; Deo, Satish Kumar (Journal of Nepal Health Research Council, 2019)
Rational use of drugs has immense impact on quality health care. Developing nations have 80% essential drug list prescription. Even though WHO estimates 15-25% antibiotics prescription in these regions, majority of Nepalese patients are prescribed more than one antibiotic in addition to inappropriate prescription in 10%-42% patients.Moreover, Nepal stands as a leading antibiotics prescribing Asian nation. Escalating irrational prescription and excessive over the counter use of antibiotics at peripheral regions of Nepal is possibly leading the emergence of multidrug resistant bacteria.Organisms like S. pneumoniae, K. pneumoniae, Salmonella spp., E. coli, N. gonorrhea, MRSA are rapidly developing first-line, second-line and multi-drug resistance in Nepal. Antimicrobial resistance is the biggest global health concern of the present day threatening the emergence of post antibiotic era. Timely intervention is must to safeguard future generation.Keywords: Antimicrobial resistance; irrational prescription; primary health care.